Study of thermal and rheological properties of PLA loaded with carbon and halloysite nanotubes for additive manufacturing. Issue 4 (13th May 2019) - Cobos, Christian Mauricio; Garzón, Luis; López Martinez, Juan; Fenollar, Octavio; Ferrandiz, Santiago
Abstract : Purpose: This paper aims to propose using polylactic acid (PLA) as an alternative to nanocomposites in additive manufacturing processes in fusion deposition modelling (FDM) systems and describe its thermal and rheological conditions with multi-wall carbon nanotube (PLA/MWCNT) and halloysite nanotube (PLA/HNT) composites for possible applications in additive manufacturing processes. Design/methodology/approach: PLA/MWCNTs and PLA/HNTs were obtained through fusion in a co-rotating twin-screw extruder. PLA was mixed with different percentages of MWCNTs and HNTs at concentrations of 0.5 Wt.%, 0.75 Wt.% and 1 Wt.%. Differential scanning calorimetry (DSC) and capillary rheometry were used to characterise these products, together with an analysis of the melt flow index (MFI). Findings: The DSC data revealed that the nanocomposites had a glass transition temperature Tg = 65 ± 2°C and a melting temperature Tm = 169 ± 1°C. The crystallisation temperature of PLA/MWCNTs and PLA/HNTs was between 107 ± 2°C and 129°C, respectively. The viscosity data of PLA/MWCNTs and PLA/HNTs obtained by capillary rheometry indicated that the viscosity of the materials is the same as that of neat PLA. These results were confirmed by the higher fluidity index in the MFI analysis. Originality/value: This paper presents an alternative for the applications of nanocomposites in additive manufacturing processes in FDM systems.